Pengembangan Media Promosi Kampus Berbasis Animasi 3 Dimensi (Studi Kasus : STMIK Palangkaraya): Development of 3D Animation-Based Campus Promotional Media: A Case Study of STMIK Palangkaraya - Rosmiati; Pratama Nugroho, Bayu; Rudini; Matatula, Frengklin; Suparno (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The rapid development of information and communication technology has created a demand for communication media that are not only fast but also engaging and easy to understand. One potential medium is three-dimensional (3D) animation, which can deliver messages in a more visual, interactive, and attractive manner. This study aims to design and develop a 3D animation as both an informational and promotional medium for STMIK Palangka Raya. The research employed observation, literature review, and interviews using questionnaires with prospective audiences to evaluate the effectiveness of the developed media. The production process followed standard animation stages, namely pre-production (story idea, storyboard, and character design), production (modeling, texturing, rigging, animation, rendering), and post-production (compositing, editing, and finalization). The resulting animation, with a duration of approximately three minutes, was created using Blender, an open-source software widely adopted in the animation industry. The final product highlights STMIK Palangka Raya’s key features, including its facilities, academic programs, student activities, and institutional strengths. Evaluation involving 18 respondents revealed positive results: 50.6% rated the animation as good, 42.4% as fair, and only 7% as poor. Specifically, the storyline received highly positive feedback (72.2%), while the background music and visual effects were also considered appropriate by the majority of respondents. These findings demonstrate that 3D animation can serve as an effective medium for higher education promotion, capable of attracting prospective students and enhancing institutional image. Moreover, the use of open-source software such as Blender provides advantages in terms of cost efficiency, flexibility, and further development opportunities